Developing Values, Strategies and Skills in Future Teachers - Cristina Frodden; Edgar Picón; Jaime Usma (Asociación Colombiana de Profesores de Ingles, 2016)
According to Colombian law, teachers should have an integral formation; that is to say, trainee teachers should develop values, skills and strategies which could help them become not only integral persons but also real educators, so that they become role models for their pupils, and can effect changes inside their social context. We are aware that students have problems not just in their academic life but in their wider personal life; therefore, we think it is important to review traditional education in order to develop more fully as human beings. We think that responsibility, commitment and interest in research are values that need to be enhanced in future teachers, as well as strategies and skills such as autonomous learning and the ability to solve problems through dialogue and to reach consensus. This implies promoting activities inside the classroom leading to such a purpose along with the specific goals of the subject to be taught.